Assessing dam spillway discharge capacity in response to extreme floods in Perak river hydroelectric scheme: Simulation and proposed mitigation measures - Azha S.F.; Sidek L.M.; Kok K.; Ahmad S.A.; Saman D.H.; Allias Omar S.M.; Basri H.; Zawawi M.H.; Ahmed A.N. (Ain Shams University, 2024)
The aged dams in Perak river Hydro-Electric Scheme (HES) have been constructed decades ago and a common concern raised during dam safety reviews is that they were not designed to safely reroute the Probable Maximum Flood (PMF) but rather the Inflow Design Flood (IDF) of 1,000 years design floods. Failure due to the insufficient spillway discharge capacity has been identified as one of the primary causes leading to overtopping. This applied research has thus been initiated to evaluate the spillway discharge capacity of dams in response to PMF extreme flooding. Besides, the safety of the dams has been evaluated by calculating the highest flood level achieved in response to the specified extreme floods. In order to simulate PMF hydrographs, various durations of Probable Maximum Precipitation (PMP) have been calculated using Hershfield statistical approach based on historical annual maximum rainfall statistics. Using a calibrated and validated hydrological model developed in HEC-HMS, PMF simulation was performed. It was discovered that the PMF generated at 120 hrs (5 days) resulted in the maximum flood level for all dams/reservoirs. The achieved highest PMF flood levels are still lower than the designated dam core and crest level in respective dams, indicating that the dams in Perak river HES are safe from overtopping failures during the occurrences of extreme events up to PMF level. While routing the worst-case scenario over 120 hr, the maximum spillway discharges predicted for Temengor and Bersia are beyond their design capacity, while Kenering and Chenderoh remain within design limits. Mitigation that will be implemented to minimize the possibility of risks to occur include improvement of emergency management system and dams monitoring data collection. It is anticipated that the outcomes of this applied research will be adopted for development of Risk Informed Decision Making (RIDM) frameworks for dams in Perak river HES in future. 2023 THE AUTHORS